2022
DOI: 10.1039/d1fo04204a
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of mixed Lactobacillus plantarum on lipopolysaccharide-induced intestinal injury in mice

Abstract: Intestine is the largest digestive and immune organ in the human body with an intact intestinal mucosal barrier. Lactobacillus plantarum is an important strain of probiotics in the intestine for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…37 TLR4, a membrane receptor, is responsible for LPS recognition and signal initiation. 38 NF-κB is a key molecule in the TLR4 signaling pathway, which regulates the expression of pro-inflammatory cytokines and induces inflammatory damage. 39 CUR is regarded as an activator of Nrf2, which plays an important role in inhibiting LPS-induced NF-κB activation and microglial activation caused by LPS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…37 TLR4, a membrane receptor, is responsible for LPS recognition and signal initiation. 38 NF-κB is a key molecule in the TLR4 signaling pathway, which regulates the expression of pro-inflammatory cytokines and induces inflammatory damage. 39 CUR is regarded as an activator of Nrf2, which plays an important role in inhibiting LPS-induced NF-κB activation and microglial activation caused by LPS.…”
Section: Discussionmentioning
confidence: 89%
“…The antioxidant effects of HO‐1 are mainly mediated by metabolites of the heme group, including bilirubin, biliverdin, carbon monoxide (CO), and free iron 37 . TLR4, a membrane receptor, is responsible for LPS recognition and signal initiation 38 . NF‐κB is a key molecule in the TLR4 signaling pathway, which regulates the expression of pro‐inflammatory cytokines and induces inflammatory damage 39 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been shown that D. vulgaris from the genus Desulfovibrio is an effective producer of acetic acid, which may be effective in reducing hepatic steatosis in mice by producing acetic acid and regulating hepatic lipid metabolism ( Hong et al, 2021 ). In addition, some probiotics or prebiotics could also significantly enhance the abundance of Desulfovibrio in mice ( Cui et al, 2022 ; Dong et al, 2022 ). Our results suggest that Desulfovibrio may play a beneficial role in the alleviation of FC by MOAE, as Desulfovibrio was significantly positively correlated with GTR and intestinal barrier factors and negatively correlated with FBST, gastrointestinal motility factors, and short-chain fatty acid content.…”
Section: Discussionmentioning
confidence: 99%
“…[12]. In experimental models of metabolic disease, Lactobacillus plantarum has been shown to have potential therapeutic effects on various conditions [13,14], such as improving hypertension [15], hypercholesterolemia [16], immunomodulation [17,18] and promoting fat loss and weight loss [19][20][21].…”
Section: Introductionmentioning
confidence: 99%